Lesbisk kärlek — längtan eller val? Politik och lesbiskt motstånd - Ehn Knobblock, Inger (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
This article deals with various strategies employed by Swedish lesbians at the end of the seventies in order to explain and defend their sexual preference. The idea of the "obligatory heterosexuality" was called into question by almost all those questioned by the RFSU (National Association for Sexual Information). Homosexuality was portrayed as being just as normal as heterosexuality by the interviewed women. Being lesbian was considered a conscious choice a woman could make irrespective of her sexual disposition. When one speaks of choosing to become lesbian, then one’s yearning for love and need of other women is understood as a conscious strategy which both bestows an affinity with others and also functions as an alternative to the masculinized heterosexual relationship. Nevertheless, caution is advisable when speaking of a "lesbian choice". Behind the political arguments for lesbianism there dwells something else, whether suitable or not — the love for another woman.